Battery Powered Wheelbarrow. (4th December 2017) - Pazdera, Ivo; Hutak, Petr; Knobloch, Jan; Prochazka, Petr; Lazek, Tomas
Abstract : The paper deals with design of independent battery powered drive for wheelbarrow and gives basic overview and comparison of various conceptions of battery powered wheelbarrow drive.